Fall report, fall 1999, Dennis Carter - Carter, Dennis L.et al (1999)
An annotated list of birds sighted by Dennis Carter. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed/flatbed